Horizontal sub drainage system in landslide risk mitigation. A case study of Shikuruwe Village, Bududa District. - Martha Ahabwe (Uganda Christian University, 2025)
Bududa District in the eastern part of Uganda faces serious risks from landslides to infrastructure and human populations. This study looked into how horizontal drainage systems can be applied to reduce the risk of landslides in Shikuruwe Village, Naposhi parish. The objectives of this study include; determining the characteristics of the site, conducting a hydrological survey of the area and designing a horizontal sub drainage system. The soil properties that were determined include the soil density, cohesion, angle of friction, shear stress and effective stress, liquid limit, soil structure. The methodology was applied according to British Standards, and the tests done included the atterberg limit tests, particle size distribution test, specific gravity and the falling head permeability test, triaxial test under unconsolidated undrained conditions and the direct shear box test under consolidated drained conditions. Spatial analysis, hydrological data, geological mapping, and field observations will also be used. Monitoring groundwater levels, conducting field surveys, and sampling soil were used to gather geological and hydrological data. Hydrological modeling and Geographical Information System were also used to develop a horizontal sub drainage system. The design of the horizontal system involved the use of software like GEOSTUDIO for slope analysis and slip surfaces, MODEFLOW for designing optimal drain configuration.. The design included considerations like drain spacing, drain length and drain configurations. The aim of the study was design optimal drainage configuration to reduce the risk of landslides happening.
Undergraduate